Body Weight Estimation of Bali Cattle in Banyumulek Techno Park, West Nusa Tenggara using Several Morphometric Parameters - Paskah Partogi Agung; Widya Pintaka Bayu Putra; Saiful Anwar; Ari Sulistyo Wulandari (Buletin Peternakan, 2018)
This study was conducted to find the best linear regression equation to estimate the body weight (BW) of female Bali cattle in Banyumulek Techno Park, West Nusa Tenggara based on three morphometric parameters, i.e. withers height (WH), body length (BL), and heart girth (HG). Data collection was conducted by random sampling of female Bali cattle (1-5 years of age) in Banyumulek Techno Park. A total of 63 female Bali cattle were used in this study. The parameter of WH (distance from the ground level to the highest point of withers) and BL (distance from the shoulder joint (later tuberosity of humerus) to the pelvic bone) were measured with a measuring stick. The HG data (circumference around the chest at the fourth rib) was measured with a measuring tape. Identification of age was carried out based on the animal recording book and incisors condition. The descriptive statistic analysis (mean value, standard deviation, the coefficient of variation, minimum and maximum value) of the morphometric and BW data were performed using MS Excel 2017 program. The linear regression equation analysis and the comparison between actual and estimated BW values (Independent sample T-test) were performed using SPSS 16.0 program. The BL and BW parameters had the highest correlation coefficient (r) value (0.86). The test result showed that the predicted BW value of female Bali cattle was not significantly different with the actual BW when using G model of linear regression equation (three variables used). The G model of linear regression equation had the highest R2 value (0.84). However the R2 value in the F model with two variables (BL and HG) was also high (0.83). It can be concluded that the simple linear regression equation BW=(0.96)(WH)+(1.26)(BL)+(1.57)(HG)-284.92 are the best model to estimate the BW value of female Bali cattle in Banyumulek Techno Park.